Microstructure and wear behavior of a refractory high entropy alloy. (June 2016) - Poulia, A.; Georgatis, E.; Lekatou, A.; Karantzalis, A.E.
Abstract: The microstructure, hardness and wear behavior of a refractory high-entropy Mo20 Ta20 W20 Nb20 V20 alloy of equi-atomic composition were evaluated. The alloy was prepared by vacuum arc melting and presented optimal empirical parameters for the formation of a solid solution phase. The lattice parameter a = 3.1867 Å for the quinary alloy was determined with high-energy X-ray diffraction. The alloy's Vickers micro hardness was estimated as HV0.5 = 7576 ± 201 MPa, while its Rockwell B hardness took a value of 97 ± 4 HRB. The exceptional hardness in this alloy is greater than any individual constituent, suggesting the operation of a solid-solution-like strengthening mechanism. The alloy's wear behavior was also studied and analyzed under different experimental conditions. The volume loss and wear rate were determined, accompanied by SEM images and EDS analysis of the wear tracks and debris, proposing some possible wear mechanisms for each case. Finally, the wear behavior of Mo20 Ta20 W20 Nb20 V20 was compared with that of a commercial superalloy (Inconel 718), proving the supremacy of the high entropy alloy concerning its wear resistance.